2018
DOI: 10.26641/2307-0404.2018.2.133954
|View full text |Cite
|
Sign up to set email alerts
|

Injuries type and its relation with Glasgow Coma Scale, injury severity score and blood transfusion in road traffic accident Victims.

Abstract: Abstract. Injuries type and its relation with Glasgow ISS (i.e., head, chest, abdominal, internal organ, pelvic)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…These include injuries to the head, spine, chest, abdomen, pelvis, and limbs. Studies have attempted to show the association between various injuries sustained from motorcycle crashes [4] . In Uganda, 41% of the RTC involve motorcycles [5] .…”
Section: Introductionmentioning
confidence: 99%
“…These include injuries to the head, spine, chest, abdomen, pelvis, and limbs. Studies have attempted to show the association between various injuries sustained from motorcycle crashes [4] . In Uganda, 41% of the RTC involve motorcycles [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Being simple and reliable, GCS is one of the most common tools used for the assessment and monitoring of a patient's level of consciousness. Studies have reported a lower GCS in patients with cardiothoracic injuries [12]. Patients with a GCS of 8 or less indicate severe thoracic trauma.…”
mentioning
confidence: 96%
“…The retrospective study of medical records conducted by Moon et al [11] validates TRISS for the assessment of thoracic trauma severity. Studies have reported a high ISS in patients with cardiothoracic injuries [12]. However, some authors have questioned the validity of ISS for assessing cardiothoracic injuries, as it is not specific for isolated thoracic trauma, and severity may be underestimated [13].…”
mentioning
confidence: 99%